KEBIJAKAN PEMERINTAH DALAM BIDANG PENDIDIKAN DARI ORDE LAMA SAMPAI ORDE BARU (Suatu Tinjauan Historis) - As’ad Muzammil (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Map of political Islam in Indonesia is always colored by the government political map. From the pre-independence era, the post-independence (old order), the new order and the reform era. Islamic education is still in a position that is generally not in favor of the empowerment of the people. Education is a tool for which the government used it to escort people and people to the desired political objectives, theoretically it is not wrong if the government wants the product graduate of educational institutions contribute to development. But at the same time the government should also give freedom to the world of education to determine its direction with permanent gets assistance, support, and facilitation from the government.